1979
DOI: 10.1007/bf00344772
|View full text |Cite
|
Sign up to set email alerts
|

Modification of egg production and packaging in response to food availability by Nassarius pauperatus

Abstract: Adjacent populations of Nassarius pauperatus differ significantly in how hungry their members are. The numbers of eggs and egg capsules produced are positively correlated with how hungry members of a population are, but the average number of eggs per capsule is negatively correlated with hunger. These results were confirmed in a laboratory experiment using two groups from the same population maintained with different levels of food.The significance of this behaviour is discussed and the hypothesis proposed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 14 publications
2
12
1
Order By: Relevance
“…This is not, however, the case for N. pauperatus from South Australia where the shell height of males is longer than that of females (McKillup and Butler 1979). The populations of N. festivus at the three study sites were female biased.…”
Section: Discussioncontrasting
confidence: 59%
“…This is not, however, the case for N. pauperatus from South Australia where the shell height of males is longer than that of females (McKillup and Butler 1979). The populations of N. festivus at the three study sites were female biased.…”
Section: Discussioncontrasting
confidence: 59%
“…It has been shown for the marine gastropod Nassarius pauperatus that when trophic conditions deteriorate, egg and egg capsule production increase (McKillup & Butler 1979). Increased reproductive effort at the expense of somatic growth has also been shown for sea urchins (Thompson 1982) and fish (Hirshfield 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, fecundity is reduced with a reduced ration (Calow & Woollhead 1977, Bayne et al 1978, Townshend & Wootten 1984, although in some species it may be enhanced (McKillup & Butler 1979, Calow 1981. In other cases, although reduced fecundity has been demonstrated, reproductive effort (that is the proportion of acquired energy allocated for reproduction) has increased (Hirshfield 1980, Thompson 1982.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated relationships between food quantity or quality and reproductive output in spionid polychaetes (Levin 1986, Grémare et al 1989, Levin 1991, Qian & Chia 1991 as well as other invertebrates (McKillup & Butler 1979, George et al 1990, George 1994. For example, Walker & Heffernan (1994) observed differences in time to spawning and gonad index with relation to level of tidal exposure of the northern quahog Mercenaria mercenaria.…”
Section: Food Availabilitymentioning
confidence: 99%